Antifungal susceptibility, species distribution and risk factors associated with mortality of invasive candidiasis in children in Turkey: A six-year retrospective, single-centre study - KEPENEKLİ KADAYİFCİ, EDA (MASSON EDITEUR, 2021)
Invasive candidiasis (IC) is a life-threatening fungal infection with high morbidity and mortality. In this study, we aimed to investigate the Candida species distribution and antifungal drug susceptibility and to identify the risk factors associated with IC mortality in children. We conducted a retrospective, single-centre study of paediatric IC in patients from a tertiary care hospital in Turkey between January 2013 and February 2019. A total of 56 Candida isolates underwent antifungal susceptibility testing performed by Sensititre YeastOne YO10 panel, and the demographic and clinical data of 65 patients were examined during the study period. The most commonly isolated species was Candida albicans in 30 patients (46%), followed by C. parapsilosis in 25 patients (38%) and C. tropicalis in three patients (5%). According to the antifungal drug susceptibility testing, C. albicans was fully susceptible to fluconazole and the other antifungal agents (100%). None of the isolates displayed resistance to anidulafungin, micafungin, flucytosine, posaconazole, voriconazole or itraconazole. There were low rates of resistance to fluconazole (1.8%), caspofungin (1.8%) and micafungin (1.8%). In addition, 5.3% of the Candida isolates were susceptible in a dose-dependent manner to itraconazole, 3.6% were susceptible to voriconazole and fluconazole and 1.8% were susceptible to anidulafungin. The mortality rate of IC was 15.4%. Thrombocytopenia after IC treatment was significantly associated with mortality in the multivariate analysis. These results, which help determine the species distribution, antifungal susceptibility patterns and risk factors for mortality, could make a significant contribution to the management of these challenging infections, including choosing appropriate empirical antifungal therapy. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Antifungal susceptibility; Invasive candidiasis; Risk factors; Mortality; Children; BLOOD-STREAM INFECTIONS; EPIDEMIOLOGY; PREVALENCE; CANDIDEMIA; SPP.